Acne vulgaris and mental health - Pawlicki, Mateusz; Łopuszyńska, Anna; Kozioł, Magdalena; Krasa, Aleksandra; Piekarska, Ewa; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2021)
Introduction: Acne vulgaris is one of the most common diseases in the world, which affects millions of people. Despite its objectively mild clinical severity, it is able to markedly change one’s appearance. Moreover it is said to be one of many factors that are responsible for mental health impairments. Results: Studies showed significant relation between acne and psychological disorders. Both depression and anxiety scores were higher in individuals with acne compared to healthy ones. Some studies reported an increased risk of suicide in this group as well. Research which included quality of life evaluation showed its impairment in larger part of respondents. Conclusions: Acne vulgaris is linked with an increased risk of serious psychiatric disorders. Therefore it is important to think about them when this condition is diagnosed.